Review: Handout Digital pada Masa Pandemi dalam Pembelajaran Kimia - Putri, Yoriska Noventi; Rinaningsih, Rinaningsih (Chemistry Education Review (CER), 2021)
The aim of this article is to examine the effects of influences during a pandemic period to improve learning outcomes in chemical materials. The method used is meta-analysis by summarizing, analyzing, and analyzing data from the literature and processed statistically. During the pandemic, teachers must be creative in learning because the learning process is carried out in a bold manner. As facilitators, teachers can facilitate students by providing digital handouts that can be accessed more easily without the internet. In addition, the use of handouts has a strong influence on improving student learning outcomes. The increase in student learning outcomes can be observed through paired sample statistical tests and the effect size of learning outcomes between before use and use of handouts. The use of handouts as an alternative to teaching materials can improve learning outcomes by 38.6%. This shows that digital material can be used as an alternative to chemical teaching materials during the pandemic.